Normoglycemia and type 2 diabetes: exploring secreted frizzled-4, insulin resistance, and waist-height ratio - Sana Akhlaq,; Saba Khaliq, (Journal of the Pakistan Medical Association, 2024)
The current study was planned to compare serum levels of secreted frizzled related protein-4, insulin resistance and waist-to-height ratio in individuals with and without a diabetic background, and to assess the correlation of these markers with family history of diabetes. The cross-sectional comparative study comprised 80 subjects with confirmed normal glucose tolerance values. Parameters assessed included secreted frizzled related protein-4, fasting glucose, random glucose, fasting insulin, homeostasis model of assessment of insulin resistance and waist-to-height ratio values. Those without a diabetic background had significantly higher frizzled related protein-4 levels (p=0.02). Although subjects with family history of diabetes showed higher mean fasting glucose, waist circumference and waist-to-height ratio, these differences were not statistically significant (p>0.05). However, there was a strong positive correlation with waist circumference, waist-to-height ratio, fasting insulin and homeostasis model of assessment of insulin resistance (p=0.0001). ---Continue